PROGNOSIS OF SKUCHERS AND PERINATAL CONDITIONS ON THE BASIS OF RESEARCH OF REGULATORY AND ADAPTATION PROCESSES IN THE SYSTEM OF MATH-PLACENT-FIT IN PREGNANCY WITH DEFICIENT OF THE MASS OF THE BODY - Елена Владимировна Рудаева; Вадим Гельевич Мозес; Игорь Сергеевич Захаров; Максим Владимирович Додонов (Медицина в Кузбассе, 2018)
Prognostic value of the indexes of the regulation of cardiothorrh of the mother and fetus in the outcome of the gestational period and childbirth with the deficiency of the body weight of the pregnant woman.